THE COMPULSORY USE OF HELMETS ON SCHOOL SKI TRIPS. Issue 17 (24th October 2013) - Stanley, M; Duncan, MJ; Price, M; Wright, S Leddington; Coad, J
Abstract : Head injuries in skiing have been a cause for concern due to the high incidence of injury particularly in young people. Furthermore, head trauma is the leading cause of death overall in skiing. Encouraging individuals to wear helmets can be problematic, especially since helmets are not compulsory in many resorts, are an additional expense and not seen as a necessity. The aim was (1) To synthesise information regarding head injuries and helmet use in young people. (2) To make a recommendation for the appropriateness of helmets use. Following ethical approval and informed consent, 101 responses were gathered from an electronic survey. This was administered to secondary schools across England which organise ski trips to identify helmet use. Electronic databases were searched for articles dating back 15 years and synthesised with grey literature as a narrative review to inform current concepts on helmet use in young people. The pooled narrative findings from literature suggest helmet use has reduced the number and severity of injuries to the head. The overall consensus is for helmets to be recommended, especially in the young. From 101 secondary schools surveyed, 96% of teachers expect young people to wear helmets whilst skiing. Discussion: The compulsory wearing of helmets in several resorts has helped to increase the awareness and importance of helmet use. A potential impact on not wearing a helmet is the concern that holiday insurance could be invalidated if injured. One British insurer now stipulates for the mandatory wearing of helmets within their policy. Findings show helmet use has been associated with a reduced risk of head injuries and the International Ski Federation recommends that all skiers regardless of ability and age use helmets. Ski helmets should be included within the ski rental package to decrease financial barriers.